2016
DOI: 10.5194/acp-2016-384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical Characteristics of Marine Fine Aerosols over Sea and at Offshore Islands during Three Cruise Sampling Campaigns in the Taiwan Strait– Sea Salts and Anthropogenic Particles

Abstract: Marine fine aerosols were simultaneously collected over sea and at offshore islands during three cruise sampling campaigns to investigate the spatial distribution of atmospheric fine particles (PM<sub>2.5</sub>) and the influences of sea salts and anthropogenic particles on the chemical characteristics of PM<sub>2.5</sub> in the Taiwan Strait. Field sampling results indicated that PM<sub>2.5</sub> concentrations over sea were generally higher than those at the offshore islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
(93 reference statements)
3
4
1
Order By: Relevance
“…Figure S9 presents the variation in levoglucosan / OC ratio along the Yangtze River. The ratio of levoglucosan / OC during this cruise ranged from 0.03 % to 0.91 % with an average of 0.35±0.24 %, which was comparable to that of Lin'an in the YRD region (Liang et al, 2017). However, the ratio of levoglucosan / OC during the YRC was near an order of magnitude lower than its value in New Delhi (3.1 ± 0.8 %) and Lumbini (3.34±2.53 %) on the northern edge of the Indo-Gangetic Plain (Wan et al, 2017), where BB plays an important role in air quality.…”
Section: Biomass Burning In Rural Regionssupporting
confidence: 56%
See 2 more Smart Citations
“…Figure S9 presents the variation in levoglucosan / OC ratio along the Yangtze River. The ratio of levoglucosan / OC during this cruise ranged from 0.03 % to 0.91 % with an average of 0.35±0.24 %, which was comparable to that of Lin'an in the YRD region (Liang et al, 2017). However, the ratio of levoglucosan / OC during the YRC was near an order of magnitude lower than its value in New Delhi (3.1 ± 0.8 %) and Lumbini (3.34±2.53 %) on the northern edge of the Indo-Gangetic Plain (Wan et al, 2017), where BB plays an important role in air quality.…”
Section: Biomass Burning In Rural Regionssupporting
confidence: 56%
“…Numerous studies have also confirmed that levoglucosan mostly originates from BB (Liang et al, 2017;Wan et al, 2017;Wang et al, 2014). The distribution of levoglucosan is irregularly parabolic from inland to coastal areas in Fig.…”
Section: Biomass Burning In Rural Regionsmentioning
confidence: 76%
See 1 more Smart Citation
“…Figure S9 presents the variation in levoglucosan / OC ratio along the Yangtze River. The ratio of levoglucosan / OC during this cruise ranged from 0.03 % to 0.91 % with an average of 0.35±0.24 %, which was comparable to that of Lin'an in the YRD region (Liang et al, 2017). However, the ratio of levoglucosan / OC during the YRC was near an order of magnitude lower than its value in New Delhi (3.1 ± 0.8 %) (Li et al, 2014) and Lumbini (3.34±2.53 %) on the northern edge of the Indo-Gangetic Plain (Wan et al, 2017), where BB plays an important role in air quality.…”
Section: Biomass Burning In Rural Regionssupporting
confidence: 56%
“…The concentrations of magnesium (Mg 2+ ) are low, ranging from 0.5 to 1.1 μg.m -3 (3.6-3.8%), and are as high as the sum of the remaining species (oxalic, formic and acetic), constituting 2.1-7.2% of the total ion mass at the ADF site. Chloride is most likely associated with sea salt origin (55% of total composition of the sea water) or secondary aerosol production (Li et al, 2016). Its highest concentration at the ADF site remains lower than the typical concentration in sea water, suggesting a secondary production source.…”
Section: Water-soluble Ionic Speciesmentioning
confidence: 98%